1971
DOI: 10.1104/pp.47.2.230
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll Synthesis in Chlorella

Abstract: The degree of light limitation of growth is the primary controlling factor of chlorophyll synthesis during photoautotrophic growth of Chlorella. The chlorophyll content of the cells increases when light is limiting for growth as occurs in dense cultures, or in cultures under low incident light, or when the light is used less efficiently through partial inhibition of photosynthesis by 3-(p-chlorophenyl)-1, 1-dimethylurea. Most algae, Chlorella included, do not require light in order to carry out chlorophyll syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

1978
1978
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 14 publications
(10 reference statements)
0
19
0
3
Order By: Relevance
“…7) maintained high chlorophyll levels. These results suggest that glucose can suppress chlorophyll synthesis in zooxanthellae, possibly as a result of end-product inhibition (14)(15)(16) X. elongata, 87 Ϯ 2%), after which it started to decrease (day 26: M. digitata, 70 Ϯ 7%; X. elongata, 75 Ϯ 6%). After the first week, many of the epithelial cells formed aggregates that adhered to the plates.…”
Section: Resultsmentioning
confidence: 91%
“…7) maintained high chlorophyll levels. These results suggest that glucose can suppress chlorophyll synthesis in zooxanthellae, possibly as a result of end-product inhibition (14)(15)(16) X. elongata, 87 Ϯ 2%), after which it started to decrease (day 26: M. digitata, 70 Ϯ 7%; X. elongata, 75 Ϯ 6%). After the first week, many of the epithelial cells formed aggregates that adhered to the plates.…”
Section: Resultsmentioning
confidence: 91%
“…Steemann-Nielsen and Hansen (1959), Rodhe et al (1966), Anderson (1969), Sayo et al (1969), Takahashi et al (1972), Eppley et al (1973) and Fee (1976) chlorophyll a increase under low light intensities. Harvey (1953), Brown and Richardson (1968), Beale and Appleman (1971) and Sheridan (1972) found an inverse proportion between light intensity and chlorophyll a concentrations for algal cells. Steele and Baird (1962), Antia et al (1963), Coombs et al (1967), Eppley (1968), Strickland et al (1969), Hobson and Pariser (1971), Thomas and Dodson (1972) and Peny (1976) showed that deficiency of P, N and Si could lead to a considerable increase in the organic carbon to chlorophyll a ratios.…”
Section: Introductionmentioning
confidence: 99%
“…As noted in chapter 3 (Table 3- was enhanced relative to total biomass in low light adapted cultures, a commonly observed response of algae (e.g. Beale and Appleman, 1971;Beardall and Morris, 1976;Prezelin, 1976;Falkowski and Ovens, 1980;Perry et al, 1981;Richardson et al, 1983). The fact that the chlorophyll ~/proteln carbon ratio declined with decreasing growth rate under low light conditions indicates that nitrogen limitation suppressed the low light enhanced chlorophyll produc tion.…”
Section: Resultsmentioning
confidence: 88%